Liquefaction-induced damage to houses and its countermeasures at Minami-Kurihashi in Kuki City during the 2011 Tohoku Earthquake, Japan. Issue 79 (December 2015) - Koseki, Junichi; Wakamatsu, Kazue; Sawada, Shunichi; Matsushita, Katsuya
Abstract: Sand boiling and liquefaction-induced damage to houses and infrastructures occurred in Minami-Kurihashi, Kuki City, during the 2011 off the Pacific Coast of Tohoku Earthquake, Japan. After the earthquake, extensive site investigations were conducted in the affected areas, including 14 borehole surveys and 43 sounding tests, where Piezo Drive Cone penetrometer, a newly developed test method, was used which could be effectively employed in detecting local change of soil profiles. A filled sandy soil layer existed near the ground surface in the affected areas, which originated from reclamation works using dredged materials to construct housing lots. In addition, a Holocene sandy soil layer existed partly at a depth of about 10–13 m. Though these two layers were evaluated to be potentially liquefiable, the liquefaction-induced damage was observed to concentrate in the areas where the reclamation works had been executed, suggesting that the liquefaction of the reclaimed layer caused such damage. It was deduced that possible liquefaction of the Holocene layer did not contribute to the damage and to the occurrence of sand boiling at the ground surface. As countermeasure against future liquefaction, ground water lowering method has been selected, and in-situ tests and numerical analyses were executed to predict the long-term ground settlement. A subsequent study on detailed design of the selected countermeasure is underway as of June 1, 2015. Highlights: Liquefaction-induced damage occurred in Minami-Kurihashi, Kuki City, Japan. The damage was concentrated in the areas where reclamation work had been executed. Possible liquefaction of natural sandy soil layer may not have added to the damage. Sounding tests using a newly-developed penetrometer could be effectively employed. As a liquefaction countermeasure, ground water lowering method has been selected.